La narrativa visual como metodología del sentido: articulación metodológica e implicaciones terapéutico-educativas - Yanes Córdoba, Víctor (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2007)
Taking as relating the currents pedagogic antiauthoritarian (based on humanist psychology) and the critical focus of the personalist pedagogies, as well as, the expressive, and transactional, focus of psychology of communication. We show that visual narrative, as a methodological instrument, can be transformed into a half dynamic, therapeutic-educational one that helps to the fellow’s active and full participation in the logic of significance of the social group: highlighting the dynamic contributions of the individuals, their social interactions, historical traditions, materials and transformations that all they suffer during the process through which you/they end up being part of an interpretation community.